MULTICULTURALISM AS AN ALTERNATIVE A CULTURAL ORIENTATION TO EDUCATION IN THE ASPECT OF CULTURE AS THE AXIOLOGICAL FOCUS - Suzanne, Rinat; Nathalie, Liana (Jurnal Ilmiah Peuradeun, 2016)
Multiculturalism occurs naturally when a society is willing to accept the culture of immigrants. Multiculturalism has been defined as a method whereby culturally diverse groups are accorded status and recognition, not just at the individual level, but in the institutional structures of the society. Multiculturalists’ perspectives have had a deep influence in the social sciences, and particularly in the field of education. Although it aims to improve society, multiculturalism has been criticized for adopting an essentialist approach to culture, because the calling for the appreciation and recognition of cultural variety. To achieve a situation in which culture has no exclusive value requires reevaluation of the concepts of culture and identity as accepted in the West over the past few centuries, examining epistemological and ontological conceptions and how they shape political and social organizations reflected in the nation-state. Just as culture is soft, permeable and dynamic, so too is the cultural self and its identity. If multiculturalism seeks a solution to distinctions that engender problems in a modern world in which many cultures are situated in one social space, we maintain that such distinctions are problematic and even erroneous. Modernity did not give rise to a multiplicity of cultures but rather to extensive cultural and social variation.